2002
DOI: 10.1163/156854002321210721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Level on Bioenergetics of the Giant Freshwater Prawn, Macrobrachium Rosenbergii (De Man, 1879) (Decapoda, Natantia)

Abstract: In order to assess the effects of dietary protein level on the bioenergetics of the giant freshwater prawn, Macrobrachium rosenbergii (De Man, 1879), animals were reared under a series of different dietary protein levels, i.e., 20%, 30%, 40%, and 50%, respectively. The prawns fed a 20% protein diet showed a signi cantly lower food intake and speci c growth rate than those fed other diets. Mean ammonia excretion of prawns in the 40% dietary protein group was signi cantly higher than that of those in the 20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Research ¢ndings suggested that dietary protein had a greater e¡ect on post-prandial metabolic response than either lipid or carbohydrate. This was later veri-¢ed by subsequent research in ¢sh as well as other animals (Tandler & Beamish1980;Peres & Oliva-Teles 2001;Du & Niu 2002). Indeed, Harper (1971) reported that SDA coe⁄cient values of protein, lipid and carbohydrate were 30%, 13% and 5% respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Research ¢ndings suggested that dietary protein had a greater e¡ect on post-prandial metabolic response than either lipid or carbohydrate. This was later veri-¢ed by subsequent research in ¢sh as well as other animals (Tandler & Beamish1980;Peres & Oliva-Teles 2001;Du & Niu 2002). Indeed, Harper (1971) reported that SDA coe⁄cient values of protein, lipid and carbohydrate were 30%, 13% and 5% respectively.…”
Section: Discussionmentioning
confidence: 81%
“…However, growth depression was reported in prawns fed diets exceeding their protein requirement due to the excess dietary protein being metabolized by the prawns as a source of energy, and nitrogen being excreted as ammonia (Burford, Thompson, McIntosh, Bauman & Pearson 2004). Du and Niu (2002) studied the effects of different dietary protein levels (200, 300, 400 and 500 g CP kg −1 ) on the bioenergetics of M. rosenbergii and found that the mean ammonia excretion of prawns fed a diet containing 400 g CP kg −1 was significantly higher than that of prawns fed diets containing either 200 or 300 g kg −1 . The standard metabolic rate of prawns fed a diet containing 300 g kg −1 protein was significantly lower than that of the prawns fed 200 and 500 g kg −1 dietary protein.…”
Section: Discussionmentioning
confidence: 99%